“They Knew Something Was Different About Me, They Date Raped Me”: A Pilot Study on the Sexual Victimization Experiences of Adolescents and Young Adults with Differences of Sex Development/Intersex Variations - Briahna Yuodsnukis; Adam Davies; Navy C. Spiecker; Jaclyn L. Papadakis; Katharine B. Dalke; Diane Chen; Tim C. van de Grift (Sexes, 2025)
Sexual and gender minority (SGM) communities experience an increased risk for sexual victimization. Because these rates are reported in aggregate, little is known about the unique experiences of sexual violence among individuals with differences of sex development/intersex variations (DSD/I). The purpose of this study is to describe the experiences of sexual victimization in adolescents and young adults (AYAs) with DSD/I as part of a larger qualitative study exploring experiences of minority stress, stigma, and resilience. Participants were recruited through multidisciplinary care clinics and DSD/I support groups in the United States and the Netherlands. Data on sexual experiences and sexual health were analyzed thematically, with a specific focus on reports of sexual victimization. Of the 20 participants, 25% reported experiences of sexual violence. Experiences were reported across gender identities and DSD/I diagnoses. Participants described experiences as (a) resulting from DSD/I, (b) exacerbated by DSD/I, or (c) healthcare practices experienced as sexual violence. Medicalization, early loss of (bodily) autonomy, and cisgender heteronormative reproductive societal norms were reported as possible factors associated with sexual victimization experiences. The sexual victimization of individuals with DSD/I appears prevalent and associated with specific risk factors and, therefore, deserves clinical and scientific attention.